Heterogeneous savers and their inflation expectation during German industrialization: Social class, wealth, and gender - Sibylle H. Lehmann-Hasemeyer; Andreas Neumayer; Jochen Streb (Humboldt University Berlin, 2022)
Using microeconomic data on 2,500 savers of the savings bank Ludwigsburg, we study individual savings behavior in 19th century-Germany. We show that wealthy savers responded to an increase in the expected inflation rate (and falling real interest rate) by increasing their savings, suggesting that they pursued a real saving target that could only be defended by saving more when investment conditions became adverse. Workers' savings behavior changed over time. For a long time, poorer, often female, working-class savers were forced to reduce their savings in times of high prices because they had to spend most of their income on essential consumer goods. This changed in the 1880s, when the living conditions of the working class improved significantly due to rising real wages and greater social security. We therefore observe a structural break in the savings regime: the originally negative relationship between inflation expectations and savings was reversed into a positive one. Looking only at the aggregate may obscure the true motives and changes in behavior of heterogeneous savers.
urn:nbn:de:kobv:11-110-18452/25054-0
Keywords: D15; E21; N33; 330; expectations; inflation; industrialization; inequality; heterogeneous savers